2007
DOI: 10.1016/j.jcf.2007.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lung transplantation on inpatient end of life care in cystic fibrosis

Abstract: Background: The impact of lung transplantation on end of life care in cystic fibrosis (CF) has not been widely investigated. Methods: Information about end of life care was collected from records of all patients who died in our hospital from complications of CF between 1995 and 2005. Transplant and non-transplant patients were compared. Results: Of 38 patients who died, 20 (53%) had received or were awaiting lung transplantation ("transplant" group), and 18 (47%) were not referred, declined transplant, or were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…Similarly, a survey of 17 CF centres in the UK and Ireland over an eight year period found that only 4% of 378 deaths had occurred at home (Cottrell, 1991). More recent reviews of hospital records indicate that over two thirds of patients with CF die in hospital (Dellon et al, 2007 andMitchell et al, 2000), reflecting both the proportion of patients receiving aggressive treatment at time of death and professionals' uncertainty over identifying the 'final illness' (Robinson, 2000).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, a survey of 17 CF centres in the UK and Ireland over an eight year period found that only 4% of 378 deaths had occurred at home (Cottrell, 1991). More recent reviews of hospital records indicate that over two thirds of patients with CF die in hospital (Dellon et al, 2007 andMitchell et al, 2000), reflecting both the proportion of patients receiving aggressive treatment at time of death and professionals' uncertainty over identifying the 'final illness' (Robinson, 2000).…”
mentioning
confidence: 99%
“…Use of mechanical ventilation and lung transplantation, first attempted for those with CF in the late 1980s, has led to a higher proportion of hospital deaths occurring within the intensive care unit (ITU), with those waiting for, or having received, lung transplant more likely to be intubated at or shortly before time of death and likely to die quickly after ventilatory support is withdrawn (Dellon et al, 2007 andFord andFlume, 2007). Although clinical outcomes of patients with CF admitted to ITU have much improved over the last two decades, under half of those currently admitted survive to hospital discharge (Vedam, Moriarty, Torzillo, McWilliam, & Bye, 2004).…”
mentioning
confidence: 99%
See 3 more Smart Citations